Proteinuria and hematuria as early signs of renal involvement in juvenile idiopathic arthritis - Del Giudice, Emanuela; Marcellino, Alessia; Hoxha, Sara; Martucci, Vanessa; Sanseviero, Mariateresa; Bloise, Silvia; De Maria, Sara Giovanna; Leone, Maria Rita; Ventriglia, Flavia; Lubrano, Riccardo (Frontiers in Pediatrics, 2024)
Objectives To evaluate glomerular and tubular renal functions and analyze blood pressure in a cohort of pediatric patients with juvenile idiopathic arthritis (JIA). Methods A total of 40 pediatric patients, 20 (50%) with JIA and 20 (50%) healthy control subjects, were studied, and performed the renal function on 24-hour collection and the 24-h ambulatory blood pressure monitoring (ABPM). Moreover, we compared renal function and blood pressure trends between the groups of JIA patients with different disease activities. Results No statistically significant differences were observed between patients with JIA and healthy children in terms of glomerular filtration rate (GFR), fractional excretion of sodium (FENa), tubular reabsorption of phosphate (TRP), and calcium-creatinine urine ratio (CaU/CrU). In contrast, we observed significantly higher values in JIA patients than in controls for the presence of hematuria (p<0.0001) and proteinuria (p<0.0001). Compared to the control group there were significantly higher values of hematuria and proteinuria/day in both groups of JIA patients with low disease activity (respectively, p=0.0001 and p=0.0002) and moderate disease activity (respectively p=0.0001 and p=0.0012). Systolic and diastolic dipping were significantly reduced in patients with JIA compared with healthy controls (p<0.0001 and p<0.0001, respectively). Conclusions Our study showed that children with JIA, already in the early stages of the disease, have higher values of hematuria and proteinuria, which are early warning signs of nephropathy. Therefore, detailed screening of renal function and pressure monitoring in patients are necessary to monitor their evolution over time.